RUTA TURISTICA DE LA PARROQUIA SANTIAGO DEL CANTÓN Y PROVINCIA DE LOJA - Martínez Yunga, Yosselyn Esperanza (2018)
Ecuador is a country recognized worldwide for its richness, variety in terms of flora as well as the fauna it has per square meter. Nowadays Ecuador allows to enjoy all kinds of tourism as adventure tourism, gastronomic, cultural, among others; which has made it an attractive destination for all kinds of tourists, practices and even ages. The province of Loja, offers a unique combination of páramo, cloud forest and jungle. In addition, its capital, the city of Loja shows the natural and cultural wonders that are in its surroundings this makes it a place or site of tourist interest. Those who arrive there are amazed with its landscapes, its indigenous markets, its colonial architecture as well as the incomparable hospitality of its people. Within the Loja Canton is the Santiago parish, where it has such a diverse wealth that it can be used to promote tourism development in the community since it contains attractions with a great variety of nature, culture, traditions, exuberant climate, the cordiality of its friendly people is added to it as hospitable, which are characteristic of the parish. In short, the parish of Santiago is apt to develop the tourist activity; it is worth mentioning that for this reason it is important to develop the research work. In this way, objectives were set, such as General Objective; "To elaborate a Tourist Route of the Parish of Santiago of the Canton and Province of Loja"., For the development of the same three specific objectives were established that are, First objective; Carry out a tourist diagnosis of the Parish of Santiago del Cantón and Provincia de Loja, the second objective was raised; Design the proposal for a Tourist Route for the Parish of Santiago del Cantón and Provincia de Loja, and as a third objective was determined; Socialize the results of the research work with the actors involved in the project. For the development of the research, research methods were used, which allowed verifying as well as fully complying with the proposed objectives; for the development of the first objective the analytical and inductive method was used, which with the help of direct observation, interviews and MARPP techniques, it was possible to break down all the information of the tourist attractions through the inventory cards of the Ministry of Tourism (MINTUR), in the same way the strengths, opportunities, weaknesses and threats were identified through the FODA matrix. For the elaboration of the second objective, the synthetic method was used where the GPS was used for the georeferencing data including the points plotted for the tourist route, also took into consideration information raised in the first objective, direct observation as well as MARPP techniques, it is important to highlight that the brand and the name named "TOURIST ROUTE SANTIAGO MÁGICO EN NATURALEZA Y CULTURA" was 5 designed, Likewise, signage was designed based on the manual of signage of the Ministry of Tourism or from Ecuador, promotion and commercialization strategies with the purpose of providing tourist facilities for the research topic. On the other hand, for the fulfillment of the third objective, the deductive method was used as well as the MARPP techniques (Rapid Analysis Method and Participatory Planning) which included three phases for the development of the socialization that are prior, execution and results that were of assistance for the development of the participatory workshop where the conclusions and recommendations in the research work were obtained. As conclusions it was determined that the tourist attractions that the Santiago parish possesses are ignored due to the lack of interest in developing promotion campaigns as well as the diffusion by the residents as well as the local authorities, the tourist route Santiago magical in nature and culture , not only aims to contribute to the proper promotion and even the dissemination of the attractions that are in it, but also this study will boost the tourist, economic development as well as the commercial of the Santiago parish. It is important to emphasize that the proposal will be established as a product that will also inform about the natural and cultural wealth that the parish presents, this in turn will allow the link to the tourist activity. To finish it is recommended to the GAD Parroquial de Santiago jointly with the Ministry of Tourism to establish participatory workshops or training for the improvement or care of the structure of the tourist image of service providers as for the integration of tourism activity to the parish , also to the tourism entrepreneurs to develop actions of renewal and regeneration of their companies, to improve the commercial image as the tourist one of the sector, on the other hand it is recommended to the authorities of the GAD Parroquial de Santiago to consider the project for its execution so that the research work is a contribution to tourism in the parish and thus improve tourism development, positioning the parish as a tourist destination of the Canton and Province of Loja.